Bounded rationality and public policy: Herbert A. Simon and the decisional foundation of collective choice - Jones, Bryan D. (2002)
By 1958, a model of humanbehavior capable of serving as the micro-level foundation for organizational and policy studies was in place, due primarily to the efforts of Herbert Simon, organization theorist James March, and computer scientist Allen Newell. Yet the fundamentals of that model, the behavioral model of choice, to this date have not been fully incorporated into policy studies and organiztional analyses. The `Simon program" remains incomplete. Much analysis continues to rely on thick or thin models of rational maximization. As is well-known, the behavioral model of choice links to organizational processes better than rational actor assumptions. But the behavioral model of choice also predicts dist tributions of organizational and policy outputs in a superior fashion, and need to draw in extraneous descriptive facets of human behavior to the analysis. As Herb Simon did beginning in 1945 until his death in 2001, I continue to advocate a solid behavioral base for the analysis of political and economic systems. - Reproduced.
Keywords: Public policy